Development of Intelligent Algorithm for Positioning a Vehicle on a Route; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Savrasov F. V. Fedor Vitalievich; Pershin E. A.; Meyta R. V. Roman Valerievich; Shamin A. A. Aleksey Alekseevich (Information Technology, Data and Signal Processing, 2016)
Title screen